Kajian Partisipasi Guru Pada Perubahan: Kontribusi Sikap Pada Perubahan Dan Persepsi Dukungan Organisasi Sebagai Variabel Moderasi - Novri Resi; Putri Intan Winarsih; Zaitul Zaitul (Journal on Education, 2024)
This study aims to determine the effect of attitudes toward change on participation in change with perceived organizational support as a moderating variable. There are three hypotheses tested in this study. The variables are measured by a five-point Likert scale ranging from strongly disagree (1) to strongly agree (5). The population of the study is teachers working in vocational schools in Pariaman city, west Sumatera, Indonesia. There are sixty-five registered teachers in this school. The primary data is employed, which is gathered through a survey. This study applies the structural equation model using smart-pls. With 54 final samples, this study reveals that (i) the attitudes toward change have a positive effect on participation in change, (ii) perceptions of organizational support have a positive effect on participation in change, (iii) perceptions of organizational support moderate the relationship between attitudes to change and participation in change This study has a practical and theoretical contribution, which are discussed in this paper.